A concise dictionary of military biography : the careers and campaigns of 200 of the most important military leaders - Windrow, Martin; Mason, Francis K. (New York : Wiley, 1975)
A concise dictionary of the most important military leaders in history, featuring detailed capsule biographies of 200 individuals from antiquity to the modern age. Included are military leaders known for their sheer genius (Genghis Khan, Frederick the Great, Napoleon); strategic ability (Wellington, Lee, Rommel, Eisenhower); incompetence or villainy (Custer, Budenny, Benedict Arnold); and administrative or theoretical mastery (Clausewitz, Liddel-Hart). Still others are included for their innovativeness (T. E. Lawrence), notoriety (Jeanne d'Arc, El Cid) or because, as with certain medieval figures, their careers are a particularly apt reflection of their times. Written by two respected authorities in the field, it is both an ideal reference for military historians and a uniquely entertaining and browsable text for general readers.
Includes bibliographical references.
Keywords: Military biography -- Dictionaries; Generals -- Biography -- Dictionaries; Generals; Military biography; Military command personnel; Biography; Dictionaries; Overseas item; Biography; Biographies; Dictionaries